The great age reboot : cracking the longevity code for a younger tomorrow - Roizen, Michael F.; Linneman, Peter; Ratner, Albert; Spiker, Ted (National Geographic, 2022)
"As the human lifespan expands and more people are living to 100 years and beyond, New York Times best-selling author Michael Roizen, M.D., explains how to prepare for a longer, healthier future"--